2008
DOI: 10.1007/s10800-008-9501-y
|View full text |Cite
|
Sign up to set email alerts
|

Anodic, cathodic and combined treatments for the electrochemical oxidation of an effluent from the flame retardant industry

Abstract: The electrochemical oxidation of an effluent from the manufacture of phosphorus based flame retardants was studied. To reach a residual concentration of reduced phosphorus lower than 10 mg L-1, in compliance with Italian law for industrial wastewater disposal, anodic oxidation using a boron-doped diamond (BDD) anode and electro-Fenton (EF) treatment were tested. The effects of some factors are optimised and a comparison of the reaction pathways is also presented. A combined treatment using EF with BDD conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The development of an electrochemical process capable of producing the Fenton reagent at selected cathodes has overcome the main drawbacks represented by the need of notable amounts of reagents and the overproduction of iron-containing sludge. Due to the results obtained, this technology has experienced a fast development and its applications over the years have ranged from treatment of dyes [4][5][6], pesticides [7,8] herbicides [9], explosives [10], surfactants [11], drugs [12,13], real effluents [14][15][16] and spent adsorbent regeneration [17].…”
Section: Introductionmentioning
confidence: 99%
“…The development of an electrochemical process capable of producing the Fenton reagent at selected cathodes has overcome the main drawbacks represented by the need of notable amounts of reagents and the overproduction of iron-containing sludge. Due to the results obtained, this technology has experienced a fast development and its applications over the years have ranged from treatment of dyes [4][5][6], pesticides [7,8] herbicides [9], explosives [10], surfactants [11], drugs [12,13], real effluents [14][15][16] and spent adsorbent regeneration [17].…”
Section: Introductionmentioning
confidence: 99%
“…The leading role of the electrochemical advanced oxidation processes (EAOPs) must be specially highlighted because they include many emerging processes that can be carried out under very mild conditions, having undergone such a development that they are not only comparable with other commonly used processes in terms of cost but also more efficient and compact [4]. Notable efforts have been done with the indirect electrochemical process called electro-Fenton (EF) and various related electrooxidation technologies, in which one or both species involved in Fenton's reaction (1) can be electrogenerated in situ from the cathodic reduction of O 2 (reaction (2)) and Fe 3+ (reaction (3)) [5][6][7][8][9][10]:…”
Section: Introductionmentioning
confidence: 99%
“…Landfill leachate Sacrificial iron anode pH 3.0 72 % COD removal in 20 minutes [184] Olive oil mill wastewater Sacrificial iron anode pH 3.0 Mineralization in 9 h at 200 mA [185] Flame retardant industry wastewater Sacrificial iron anode pH 1.5 99.9 removal of P-compunds [149] Petrochemical industry wastewater (49) Production of radicals from chlorine has been also described in literature [97,98], being demonstrated that under non extreme pH, hydroxyl and chlorine radicals are the main end products resulting of the light assisted degradation of hypochlorite.…”
Section: Electro-fentonmentioning
confidence: 99%